Mechanical Properties of ARMCO® Iron after Large and Severe Plastic Deformation—Application Potential for Precursors to Ultrafine Grained Microstructures - Enrico Bruder (Metals, 2018)
Ultrafine grained (UFG) metals processed by severe plastic deformation (SPD) are well known for their outstanding mechanical properties, yet, current applications are very limited mostly due to the elaborate processing. The present work investigates the microstructures and mechanical properties of precursors to UFG microstructures that evolve at strains below the levels required for UFG microstructures, which implies less processing effort. ARMCO® iron is subjected to a single pass of equal channel angular pressing (ECAP), cold rolling, as well as a combination of both processes and compared to strain–free samples and a UFG reference condition subjected to five ECAP passes. All conditions are characterized regarding their microstructures and mechanical properties using electron backscatter diffraction, tensile tests, and rotating bending fatigue test. The precursor states show intermediate properties in between those of the strain-free and the UFG reference condition. Compared to the processing effort, the difference in properties between precursors and UFG reference is relatively small. Especially a combination of a single ECAP pass followed by cold rolling is a good compromise in terms of processing effort and mechanical properties with an endurance limit being less than 10% lower as compared to the UFG reference condition.